2022
DOI: 10.14712/23362936.2022.4
|View full text |Cite
|
Sign up to set email alerts
|

Effective Treatment of a Melanoma Patient with Hemophagocytic Lymphohistiocytosis after Nivolumab and Ipilimumab Combined Immunotherapy

Abstract: Immune checkpoint inhibitors have significantly improved the prognosis of melanoma patients. However, these therapies may trigger unexpected immune-related adverse events (irAEs), which are challenging in making the proper diagnosis and providing treatment. Hematological toxicities are possible irAEs, but were poorly evaluated in clinical trials and treatment recommendations of this specific complications are limited. We present a stage IV melanoma patient who developed an extremely rare toxicity – hemophagocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The high discontinuation rate due to AEs (almost 40% in our study) and too early treatment withdrawal (38% of patients received less than 4 series) despite the lack for PD seems to be the wrong strategy. Prompt AEs management and, if possible, immunotherapy continuation are important since they might improve the patient’s prognosis as we demonstrated in the case report from our clinic [ 43 ]. For example, a study from Nova Scotia demonstrated that only half of immunotherapy-related AEs are managed according to guidelines and about 17% of discontinued patients were withdrawn too early for this reason [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high discontinuation rate due to AEs (almost 40% in our study) and too early treatment withdrawal (38% of patients received less than 4 series) despite the lack for PD seems to be the wrong strategy. Prompt AEs management and, if possible, immunotherapy continuation are important since they might improve the patient’s prognosis as we demonstrated in the case report from our clinic [ 43 ]. For example, a study from Nova Scotia demonstrated that only half of immunotherapy-related AEs are managed according to guidelines and about 17% of discontinued patients were withdrawn too early for this reason [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…) Resolution AIHA, auto-immune hemolytic anemia; CLL, chronic lymphocytic leukemia; Dab/Tram, dabrafenib/trametinib; DAT, direct antigen test; HLH, hemophagocytic lymphohistiocytosis; ICI, immune checkpoint inhibitor; Ipi, ipilimumab; irAE, immune-related adverse event; MM, mycophenolate mofetil; Nivo, nivolumab; Pembro, pembrolizumab[17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
mentioning
confidence: 99%